2019
DOI: 10.1097/dcr.0000000000001261
|View full text |Cite
|
Sign up to set email alerts
|

Partial Stapled Hemorrhoidopexy Versus Circumferential Stapled Hemorrhoidopexy for Grade III to IV Prolapsing Hemorrhoids: A Randomized, Noninferiority Trial

Abstract: BACKGROUND:Long-term outcomes and efficacy of partial stapled hemorrhoidopexy are not known.OBJECTIVE:The purpose of this study was to compare the long-term clinical efficacy and safety of partial stapled hemorrhoidopexy with circumferential stapled hemorrhoidopexy.DESIGN:This was a parallel group, randomized, noninferiority clinical trial.SETTINGS:The study was conducted at a single academic center.PATIENTS:Patients with grade III/IV hemorrhoids between August 2011 and November 2013 were included.INTERVENTION… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 31 publications
0
18
0
Order By: Relevance
“…For the remaining studies, the full texts were obtained and reviewed. Seven studies were excluded based on reasons listed in Table 1 [12][13][14][15][16][17][18]. Cumulatively, 17 articles (15 case reports and two case series) were considered relevant, and 38 patients were included ( Figure 1, Seven papers reported perirectal hematoma [3,17,18,[20][21][22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the remaining studies, the full texts were obtained and reviewed. Seven studies were excluded based on reasons listed in Table 1 [12][13][14][15][16][17][18]. Cumulatively, 17 articles (15 case reports and two case series) were considered relevant, and 38 patients were included ( Figure 1, Seven papers reported perirectal hematoma [3,17,18,[20][21][22][23][24][25][26][27].…”
Section: Resultsmentioning
confidence: 99%
“…For the remaining studies, the full texts were obtained and reviewed. Seven studies were excluded based on reasons listed in Table 1 [ 12 , 13 , 14 , 15 , 16 , 17 , 18 ]. Cumulatively, 17 articles (15 case reports and two case series) were considered relevant, and 38 patients were included ( Figure 1 , Table 2 ) [ 3 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Regarding Scenario 2, diverticulum formation does not necessarily result from failure to achieve complete resection along the circumference of the anastomosis. In terms of postoperative complications after SH, a recent study reported partial SH as a new procedure to potentially reduce the rates of several morbidities associated with conventional SH, including anastomotic stenosis, rectovaginal fistula, defecatory dysfunction, and RPS [13]. Additionally, the partial SH procedure, which is performed by preserving the mucosal bridges, is noninferior to SH.…”
Section: Discussionmentioning
confidence: 99%
“…Today, hemorrhoids are characterized by their relevance among coloproctological diseases. There is many data on the pathogenesis and course of hemorrhoidal disease, the clinical picture of hemorrhoids, which is diverse in a wide range and requires careful differential diagnosis [1,2,3].…”
Section: Introductionmentioning
confidence: 99%